ENGAGING INFORMAL CAREGIVERS IN CLINICAL RESEARCH: USING DYADIC INFORMATION TO PREDICT WHO WILL PARTICIPATE. (11th November 2018) - Mogle, J; Juarez, R; Vellone, E; Buck, H
Abstract: Increasingly research in heart failure (HF) and related areas on other complex, chronic conditions (e.g., diabetes) includes informal caregivers whether for observational purposes to understand how informal caregivers support the patient in self-care or for interventional purposes to directly involve the informal caregiver in symptom management. However, dyadic participation in research studies requires additional effort from the researcher to recruit, enroll, and obtain the data required for eventual analysis. Missing data due to poor caregiver compliance remains an issue and identifying predictors of caregiver participation would improve recruitment efforts. The current project examined likelihood of caregiver completion in two projects as predicted by dyadic self-care type, a measure of whether patients and caregivers work together to manage the patients' HF symptoms. In study one, patients (N=68, Mage=73.0, 63% Male) were only recruited if a caregiver was immediately present at the appointment (restricted condition). In study two, patients (N=178, Mage=81.1, 50% Male) were recruited and a caregiver was contacted only after the patient was enrolled (unrestricted condition). In the restricted condition, caregivers were more likely to participate when their dyadic self-care approach was collaborative, though this was not true in the unrestricted condition. In the unrestricted condition, caregiver participation was highest when patients indicated their caregiver took care of most of their HF management. We will discuss the utility of using a dyadic assessment early in recruitment and screening processes to determine the effort that will be needed to engage caregivers in research participation.